Aplikasi Perhitungan Gaji dan Pendistribusian Slip Gaji melalui E-mail Karyawan: Aplikasi Perhitungan Gaji dan Pendistribusian Slip Gaji melalui E-mail Karyawan - Cut Ranti Dwi Shintia; Taqrim Ibadi (Teknik Komputer Politeknik Negeri Sriwijaya, 2023)
PT Lematang Coal Lestari is a company engaged in coal mining. The salary calculation system that is currently running at the company is carried out using the Microsoft Excel application, this can affect data security. In addition, the distribution of salaries is still printed one by one and then distributed to each representative department, this is certainly not safe in the confidentiality of salary data for each employee and does not apply health protocols in the current COVID-19 pandemic. Given this problem, it is therefore necessary to apply salary calculations and distribute salary slips automatically via employee e-mail with the aim of assisting in data processing so that they can overcome human errors or errors in Microsoft Excel data, so that data becomes more secure and accurate. The research methodology used is a qualitative research method where data collection is done through observation and interviews. The system development method used is the waterfall method and the framework used in writing code is CodeIgniter 3. Keywords— Application; Employees; Salary.